Priorities of development of oil and gas branch Republic of Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
The main task of the energy strategy of the Republic of Kazakhstan is how to achieve a qualitatively new state of the fuel and energy complex, increasing the competitiveness of its products and services in the global market through the use of capacity and prioritization of development complex formation measures and mechanisms of state energy policy,taking into account the anticipated results of its implementation . With the development of globalization , increase in the volume of foreign economic relations , the problem of competitive development and competitiveness of the national economy and its economic entities became one of the central . Oil and gas sector is an integral part of the national economy, and he, in varying degrees, many of its inherent shortcomings and problems. The problem of improving the competitiveness requires a number of scientific, technical, industrial, economic, social and environmental objectives. All these problems of oil and gas complex of Kazakhstan and the focus of this article.
Keywords: oil and gas branch; stocks of hydrocarbonic resources; rational use of raw materials; oil processing; petrochemistry; oil refinery; restructuring